2014
DOI: 10.4049/jimmunol.1301556
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Modulates Autoantibody Production and Skin Blistering in Experimental Epidermolysis Bullosa Acquisita

Abstract: GM-CSF activates hematopoietic cells and recruits neutrophils and macrophages to sites of inflammation. Inhibition of GM-CSF attenuates disease activity in models of chronic inflammatory disease. Effects of GM-CSF blockade were linked to modulation of the effector phase, whereas effects on early pathogenic events, for example, Ab production, have not been identified. To evaluate yet uncharacterized effects of GM-CSF on early pathogenic events in chronic inflammation, we employed immunization-induced epidermoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…Neutrophil activation was assessed by the determination of IC-induced ROS release using a previously published protocol50 with minor modifications. In brief, the mouse femurs were isolated, and the cells were washed out with 10 ml PBS using a 26 G syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil activation was assessed by the determination of IC-induced ROS release using a previously published protocol50 with minor modifications. In brief, the mouse femurs were isolated, and the cells were washed out with 10 ml PBS using a 26 G syringe.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated TCRγδ or NKT cells were restimulated for 18 h using 5 μg/ml anti mCD3 (Biolegend, clone 145-2C11). The cultured cells, the supernatant or the combination of both was subsequently co-cultured with freshly isolated murine neutrophils50 in a ratio of 1:4 for additional 4 h. The neutrophils were stained for FACS using CD18-FITC, CD62L-PE-Vio770, Ly6G-APC-Vio770 and CD45-VioGreen (Miltenyi) following standard procedures to evaluate the activation status. Dead cells were excluded using PI.…”
Section: Methodsmentioning
confidence: 99%
“…In one recent study it was demonstrated that GM-CSF treatment could exacerbate autoantibody production and skin blistering in experimental epidermolysis bullosa acquisita (EBA) through neutrophil activation. Predictively, neutralization of GM-CSF proved to be beneficial in this model (63). However, how GM-CSF affects autoantibody production is not understood.…”
Section: Introductionmentioning
confidence: 97%
“…However, recent evidences suggest the involvement of neutrophils in various autoimmune diseases in human including rheumatoid arthritis (58, 60), systemic lupus erythematosus (61), Bullous pemphigoid (62), Epidermolysis bullosa acquisita (63), multiple sclerosis (64) and anti-neutrophil cytoplasmic autoantibodies-associated vasculitis (65). Neutrophils participate in almost every phase of autoimmune diseases such as immunization, transition and effector phase.…”
Section: Introductionmentioning
confidence: 99%
“…Additional work using an adult mouse model for EBA demonstrated that the alternative complement pathway, [35] neutrophils, CD18, NADPH oxidase, [36] GM-CSF, [37] IL-6, [38] TNF-α, [39] Hsp90, [40] CXCR1/2 [41] and the neonatal Fc-receptor [42] are crucial for the pathogenesis of experimental EBA. To avoid the non-specific effects of high levels of rabbit IgG, this model was refined using affinitypurified IgG.…”
Section: Antibody Transfer-induced Models Of Ebamentioning
confidence: 99%